Synthetic Aperture Radar Simulation for Point and Extended Targets - Adewoye, Akintunde (My University, 2013)
Basic radar systems use electromagnetic wave reflections from targets to determine the motion characteristics of these targets. Synthetic Aperture Radar (SAR) systems use the reflections to produce target images as well. SAR is an imaging radar system that produces high resolution images of a scene or target by using radar motion to synthesize the antenna aperture. A SAR model to handle extended targets and point targets in faster time is presented, as are some simulated results. This thesis explains synthetic aperture concepts, the model used and a simulation of a SAR system. It runs through modelling point targets as well as extended targets by using the resolution cells of the radar, creating the raw signal data from the target information and then the signal processing that converts the raw data to a SAR image. The simulation was done for better understanding of synthetic aperture parameters and it was done in C++ programming language for improved processing speed. In comparison to previous simulations obtained from literature review, there is an increase in speed of more than 2.5 times as the number of targets increases, producing higher resolution images in less time. A model to handle extended targets was presented while also showing the imperfections due to the model assumptions. These assumptions are then explained as the best option in the absence of extra geographic information on the target scene.
Keywords: SAR; Synthetic Aperture Radar; radars; SAR model; extended target RCS; extended target RCS model; Electrical and Computer Engineering; Signal Processing; Electrical and Computer Engineering